Characterization of the alluvial fan of the Cave creek in the town of Maramara, NE Lima - Lopez Abanto, Wilson (2013)
This survey consist of the field work, mainly focused at the development of sedimentary logs, as well as the field observations of the bulk of the processes that give rise to the different parts of an alluvial fans. This study tackles from sedimentology and cartography skills for unveiling the key physical processes involved at the genesis of similar topographic shapes in Lima province surroundings.